Waste management in the hospitality industry in Astana. A comparison of three companies and recommendations to maintain ecologically responsible business - Kairatkyzy, N.; Kozhakova, D. (M. S. Narikbayev KAZGUU University School of Liberal Arts, 2023)
The hospitality sector produces significant quantities of waste that may have adverse environmental effects, increase costs and damage reputation if it is not managed effectively. The objective of the project: to compare the waste management practices of three hotels in Astana: Rixos President Hotel Astana, the St Regis Hotel Astana and the Radisson Hotel Astana. Relevance of the project: in order to reduce negative environmental effects, improve hotel reputation and ensure sustainable tourism development, the management of waste is crucial in the hospitality sector. While in the hospitality sector waste management has been extensively investigated, there is still a lack of research into hotel waste management practices in Kazakhstan
Keywords: *